UPAYA MENCARI KEBENARAN MATERIIL DALAM HUKUM ACARA PERDATA - Lubis, Fauziah; Sinambela, Naura Fitri Zaskia; Syahputri, Ardita; Meha, Mellisa; Syahputri, Tri; Lubis, Fahrul Ramadhan (Gapenas Publisher, 2025)
This study aims to examine the application of the principle of material truth in civil procedural law in Indonesia and compare it with the concept of formal truth that has been dominant so far. The problems raised in this study are: how is the application of the principle of material truth in civil procedural law in Indonesia, and what is the difference between material truth and formal truth in civil procedural law. The background of this study is based on the fact that the Indonesian civil procedural law system, which historically adheres to an adversarial system and emphasizes formal truth, in practice allows judges to actively explore substantive truth in order to achieve justice. This study uses a normative juridical method with a statutory and conceptual approach. Data obtained from primary and secondary legal materials were analyzed descriptively qualitatively. The results of the study show that although Indonesian civil procedural law emphasizes formal evidence, in practice there is a tendency to apply the principle of material truth, especially in cases concerning the public interest or inequality between the parties. Thus, the principle of material truth has important relevance in realizing substantive justice in resolving civil disputes.